ON CORRELATION OF THE CONCEPTS OF «CRIME», «CRIMINAL OFFENSE», «ADMINISTRATIVE OFFENSE» - Karzhaubayev, Серик Сеитович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2021)
Decriminalization and humanization of legislation requires the development of new concepts and their relationship. Therefore, the definition and correlation of the concepts of «crime», «misdemeanor» and «administrative offense» is the most relevant. The article provides a brief overview of the history of these concepts from the common law to the modern era. The author suggests that at all times there were crimes and misdemeanors, and the bias of legislation in one direction or another was caused by the need for the criminal policy of the state at that time. Thus, the Soviet period is characterized by the predominance of criminal legislation and the complete absence of administrative legislation. Further decmocratization of legislation in Kazakhstan led to the emergence of such concepts as «administrative law violation» in 1984 and «misdemeanor» in 2014. «Criminal misdemeanor» was defined as a «criminal offense» as it is characterized by the presence of mandatory features inherent in the «crime», but differing in the degree of public danger and the punishability of the acts. The concept and correlation of the concepts of «crime» and «criminal offense» are clearly formed in the criminal legislation, but require clarification of the concept of «criminal offense». The author presents a position regarding the definition of «criminal offense». Noting the concept of «administrative offense», the author highlights the completeness of such a definition in the administrative-tort legislation. At the same time, the ratio of «administrative offense» and «criminal offense» is based on the similarity of the offense and the administrative offense. The author, using the example of some similar norms, notes the disproportion of punishment and punishment, the incorrect orientation of practical bodies when considering hooligan manifestations. The idea is expressed about the haste of attributing beatings to the category of administrative offenses. The author comes to the conclusion that the existing definition of the concept of administrative offense, criminal misdemeanor and crime sufficiently fully and comprehensively reflects all aspects inherent in these concepts and does not need to be finalized.